CURRENT GEOMORPHOLOGICAL PROCESSES IN THE SOUTH OF GUTÂI MOUNTAINS - ANDRON, D.; IRIMUŞ, I.A. (Studia Universitatis Babeș-Bolyai Geographia, 2019)
The current geomorphological processes that are highly aggressive in the south of Gutâi Mountains have been identified during onsite visits carried out between 2014 and 2017. The analysis on the landscape impact has been carried out by using GIS methodology. The pluvio-denudation mainly occurrs within the areas unraveled by the topsoil of the piedmont. The linear erosion is located within areas with a suitable slope for such processes and with a lithology that would allow their development (clay and sandy clay). Taking into account the elevated aspect of volcanic morphostructures, they resulted in the concurrence of the gravity processes as follows: collapsing and rolling, together with a pseudo-soil-flowing area located within the upper section of Șatra Massif. An original aspect of this is the identification of suffosion processes, as represented by a series of five suffosion cones placed on one alignment, and joined through a suffosion channel.